2008
DOI: 10.1093/mp/ssn019
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Defense Response Pathways by OGs and Flg22 Elicitors in Arabidopsis Seedlings

Abstract: We carried out transcriptional profiling analysis in 10-d-old Arabidopsis thaliana seedlings treated with oligogalacturonides (OGs), oligosaccharides derived from the plant cell wall, or the bacterial flagellin peptide Flg22, general elicitors of the basal defense response in plants. Although detected by different receptors, both OGs and Flg22 trigger a fast and transient response that is both similar and comprehensive, and characterized by activation of early stages of multiple defense signaling pathways, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
499
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 463 publications
(551 citation statements)
references
References 124 publications
(150 reference statements)
46
499
3
3
Order By: Relevance
“…CML41 expression was previously shown to be upregulated by flg22 (Denoux et al ., 2008), so we investigated whether it had a role in pathogen responses. First, we confirmed that CML41 transcription was induced flg22 using quantitative RT‐PCR and expression analysis of the CML41 promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CML41 expression was previously shown to be upregulated by flg22 (Denoux et al ., 2008), so we investigated whether it had a role in pathogen responses. First, we confirmed that CML41 transcription was induced flg22 using quantitative RT‐PCR and expression analysis of the CML41 promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, both elicitors induce changes in nuclear and cytosolic Ca 2+ concentrations, yet the changes vary in magnitude and timing (Lecourieux et al, 2005). Whereas cryptogein induces a well-characterized HR in tobacco plants and cell death in suspension cells, flagellin acts as a nonnecrotic elicitor (Denoux et al, 2008). Moreover, cryptogein induces a dramatic depolymerization of cortical microtubules in tobacco cells after 1 h of treatment (Binet et al, 2001), whereas flg22 did not cause any such changes in the radial or cortical microtubules (Guan et al, 2013).…”
Section: Cryptogein Transiently Induces a Modification In Tobacco Celmentioning
confidence: 99%
“…To confirm the link between triggering of defense signaling and RGM modification, we used flg22, a known activator of plant defense mechanisms (Denoux et al, 2008), especially in tobacco cells (Lecourieux et al, 2002). The timing and intensity of the reactive oxygen species (ROS) productions triggered by flg22 (20 nM) and by cryptogein were comparable (Supplemental Fig.…”
Section: Transient Modifications Of Pm Biophysical Properties Occur Umentioning
confidence: 99%
See 1 more Smart Citation
“…Seedlings were examined for the expression of genes that are induced early in response to both OGs and elf18 (Kunze et al, 2004;Denoux et al, 2008). We chose FRK1, a flagellinresponsive receptor-like kinase gene, the expression of which is considered to be strictly regulated by the MAPK cascade (Boudsocq et al, 2010), RET-OX, encoding a protein with homology to reticuline oxidases (Dittrich and Kutchan, 1991), and CYP81F2, encoding a cytochrome P450 involved in indol-3-yl-methyl glucosinolate catabolism (Clay et al, 2009).…”
Section: Anps Do Not Play a Major Role In Og-auxin Antagonismmentioning
confidence: 99%